DNA Finger Printing and its Medico Legal Importance (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
The use of DNA finger printing in solving crime is proving to be as revolutionary as the introduction of fingerprint evidence in court more than a century ago. It has emerged as one of the most powerful tools available for solving many medical as well as legal complexities. The DNA molecule is very stable and can withstand significant environmental challenge which enables forensic scientists to obtain new information from very old biological evidence or establish important data from badly degraded samples. The stability of molecule combined with the discrimination features of each individual’s DNA and the accuracy of current DNA analysis techniques, makes this technology a vital component of a number of medico-legal investigations.
Keywords: De-oxyribose nucleic Acid; DNA fingerprinting; DNA Probe; Polymerase Chain reaction